You are on page 1of 2

Derivation of the Black-Scholes formula from the risk-neutral

expectation

The price of a European call option at a generic point in time t can be written as a
discounted risk-neutral expectation of the payoff at option’s maturity T :

Ct = e−r(T −t) EQ [max{ST − K, 0}|Ft ].

As a shorthand notation, let us introduce EQ [· · · |Ft ] ≡ EQ
t [· · ·] for risk-neutral expectation
conditional on the information available at time t, and Q[· · · |Ft ] ≡ Qt [· · ·] for risk-neutral
probability conditional on the information available at time t. Then,

Ct = e−r(T −t) EQ
t [max{ST − K, 0}]
= e−r(T −t) EQ [ST − K|ST ≥ K]
ht i
= e−r(T −t) EQ Q
t (ST |ST ≥ K) − Et (K|ST ≥ K)
h i
= e−r(T −t) EQ Q
t (ST |ST ≥ K) − KEt (1|ST ≥ K)
h i
= e−r(T −t) EQ t (ST |ST ≥ K) − KQt (ST ≥ K)
h i
(r−σ 2 /2)(T −t)+σ(WT −Wt )
= e−r(T −t) EQ t (S t e |S T ≥ K) − KQ (S
t T ≥ K)
h 2
i
= e−r(T −t) St e(r−σ /2)(T −t) EQ t (e σ(WT −Wt )
|S T ≥ K) − KQ (S
t T ≥ K) .

As WT − Wt | Ft ∼ N (0, T − t), we can write WT − Wt = ε T − t, where ε ∼ N (0, 1)
i.i.d. Also, note that ST ≥ K can be written as:
2 /2)(T −t)
ST ≥ K ⇐⇒ St e(r−σ eσ(WT −Wt ) ≥ K

⇐⇒ ln(St ) + (r − σ 2 /2)(T − t) + εσ T − t ≥ ln(K)

⇐⇒ ln(St /K) + (r − σ 2 /2)(T − t) + εσ T − t ≥ 0
⇐⇒ ε ≥ −d2 ,

where
ln(St /K) + (r − σ 2 /2)(T − t)
d2 = √ .
σ T −t
At this point we can also define

ln(St /K) + (r + σ 2 /2)(T − t) √
d1 = √ = d2 + σ T − t
σ T −t
for further reference.

2 . √ σ(WT −Wt ) σε T −t EQ t (e |ST ≥ K) = EQ t (e |ST ≥ K) √ σε T −t = EQ (e |ε ≥ −d2 ) Z t∞ √ σε T −t = e f (ε)dε Z−d ∞ 2 √ T −t 1 2 = eσε √ e−ε /2 dε 2π Z−d ∞ 2 √ 1 2 = √ eσε T −t e−ε /2 dε. Hence. Putting everything together. −d2 2π Complete the squares. h 2 i Ct = e−r(T −t) St e(r−σ /2)(T −t) EQ t (eσ(WT −Wt ) |S T ≥ K) − KQt (S T ≥ K) h 2 2 i = e−r(T −t) St e(r−σ /2)(T −t) eσ (T −t)/2 N (d1 ) − KN (d2 ) = St N (d1 ) − Ke−r(T −t) N (d2 ). √ where x = ε − σ T − t. Similarly. We proceed from here by calculating the expectation and the probability by definition. Z ∞ √ σ(WT −Wt ) 1 2 EQ t (e |ST ≥ K) = √ eσε T −t e−ε /2 dε ε=−d2 2π Z ∞ σ 2 (T −t)/2 1 2 = e √ √ e−x /2 dx x=−d −σ T −t 2π Z ∞ 2 2 = eσ (T −t)/2 f (x)dx x=−d1 σ 2 (T −t)/2 = e [1 − N (−d1 )] σ 2 (T −t)/2 = e N (d1 ). √ √   σε T −t −ε2 /2 1 2 e e = exp − ε − 2σε T − t 2 √   1 2 2 2 = exp − ε − 2σε T − t + σ (T − t) − σ (T − t) 2 √     1 2 1 2 = exp − ε − σ T − t) exp σ (T − t) 2 2 2 /2 2 (T −t)/2 = e−x eσ . Z ∞ Qt (ST ≥ K) = f (ε)dε −d2 = [1 − N (−d2 )] = N (d2 ).